2003
DOI: 10.1093/annonc/mdg449
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial combining docetaxel and doxorubicin as neoadjuvant chemotherapy in patients with operable breast cancer

Abstract: Docetaxel and doxorubicin is an effective and well-tolerated combination in the neoadjuvant therapy of breast cancer. Future controlled trials are warranted to investigate the best schedules and to correlate response with biological factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…Swain et al [3] reported that 3-5 cycles were optimal to achieve partial and complete responses, respectively. Ganem et al [25] reported that 6 cycles of doxorubicin and docetaxel were optimal for operable breast cancer with tolerable toxicity. Nonetheless, the overall response rate (85%) and pCR (15%) are similar to other reports in which patients received 3 or 4 cycles of combination PST [8]; however, 12% of patients did not complete the whole 6-cycle regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Swain et al [3] reported that 3-5 cycles were optimal to achieve partial and complete responses, respectively. Ganem et al [25] reported that 6 cycles of doxorubicin and docetaxel were optimal for operable breast cancer with tolerable toxicity. Nonetheless, the overall response rate (85%) and pCR (15%) are similar to other reports in which patients received 3 or 4 cycles of combination PST [8]; however, 12% of patients did not complete the whole 6-cycle regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Four Phase II studies have evaluated docetaxel in combination with doxorubicin [36][37][38][39]. In the earliest study by von Minckwitz et al [38], a dose-dense AT schedule yielded one of the highest clinical tumour response rates reported in the literature.…”
Section: Docetaxel-anthracycline Concomitant Regimensmentioning
confidence: 99%
“…Results of two further studies of primary AT in traditional 3-weekly schedules are available [36,37]. Preliminary results currently published in abstract form by Valero et al [37] show that for 70 patients with stage III-IV breast cancer, a clinical ORR of 90% (CR 4%) and a complete pathological response rate of 10% can be achieved with AT.…”
Section: Docetaxel-anthracycline Concomitant Regimensmentioning
confidence: 99%
“…Neoadjuvant treatment is commonly used to treat advanced tumors. [13][14][15][16][17] Consequently, many patients must undergo major surgery while chemotherapy is active; however, it is well known that chemotherapy impairs wound healing, which increases morbidity and prolongs hospitalization. 3,[18][19][20][21][22][23][24] Adriamycin is a wide-spectrum anthracycline group chemotherapeutic agent, which is frequently used but has many side effects.…”
Section: Discussionmentioning
confidence: 99%